KEADILAN ORGANISASIONAL SEBAGAI PEMEDIASI PENGARUH KEPEMIMPINAN ETIS TERHADAP COUNTERPRODUCTIVE WORK BEHAVIOUR PADA HOTEL DISCOVERY KARTIKA PLAZA KUTA - Wiratama, William Jefferson; Riana, I Gede; Rahyuda, Agoes Ganesha (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
This study aims to determine the influence of ethical leadership and organizational justice on counterproductive work behavior and to know the role of organizational justice in mediating the effects of ethical leadership to counterproductive work behavior. The sample are 142 Discovery Kartika Plaza Hotel Kuta employees, using probability sampling method. This study used the PLS (Partial Least Square) analysis. The result is that ethical leadership had negative and significant impact on counterproductive work behavior. Organizational justice also found to have a negative and significant impact on counterproductive work behavior. Furthermore, justice organization proved to partially mediate the influence of ethical leadership to counterproductive work behavior. This study implicates that employees pay more attention to organizational justice as their benchmark to remain loyal to the organization as indicated by the low level of employment deviations that occur. It is important for top management Discovery Kartika Plaza Hotel's to give attention to distributive justice as a major factor that determines the reflection of organizational justice.
Keywords: ethical leadership, organizational justice, counterproductive behaviour